Assessing safety of negative-pressure wound therapy over pedicled muscle flaps: A retrospective review of gastrocnemius muscle flap. Issue 4 (April 2016) - Lance, Samuel; Harrison, Lindsey; Orbay, Hakan; Boudreault, David; Pereira, Gavin; Sahar, David
Summary: The use of negative-pressure wound therapy (NPWT) for management of open wounds and immobilization of split-thickness skin grafts (STSGs) over wounds has been well described. However, there is a concern for potential compromise of flap viability when NPWT is used for skin grafts over pedicled muscle flaps. We have used NPWT to immobilize STSGs in eight patients who underwent a pedicled gastrocnemius muscle flap operation in our department. We applied a negative pressure of −75 mmHg on the muscle flaps for 5 days postoperatively. All wounds healed successfully, with a 97.5 ± 5.5% mean STSG uptake. No flap necrosis was observed. In our series, the use of NPWT for fixation of STSGs over pedicled gastrocnemius muscle flap was effective and had no negative impact on flap viability.